Polymer Science and Engineering : Selected, peer-reviewed papers from the 3rd International Conference on Composite Material, Polymer Science and Engineering (3rd CMPSE), October 24-25, 2019, Bangkok, Thailand - Kida, Katsuyuki (Key engineering materials ;, 2020)
The proceeding book contains papers from the 3rd International Conference on Composite Material, Polymer Science and Engineering (3rd CMPSE), which was held on October 24th and 25th, 2019 in Bangkok, Thailand. The main topics are technologies of materials joining; mechanical properties and mechanical testing; properties of functional materials, composites, polymer composites, and fibers; properties of materials and structures in construction. Composites, Polymer Composites, Alloy, Steel, Joining Technologies, Welding, Friction Stir Forming, Thermoplastics, Ceramics, Cermet, Functional Materials, Building Materials, Structural Elements Materials Science, Building Materials, Mechanical Engineering.